A legal aspect on marketing of infant formula milk / Munirah Zahid ... [et al.] - Zahid, Munirah; Norazlan, Nurul Nadzirah; Mohamed, Nor Atikah (2013)
The purpose of this project paper is to focus on the legal aspect on marketing of infant formula milk. It further moves on to the theories of marketing by the manufacturers of infant formula milk in Malaysia throughout the industrial revolution of marketing. This research proves that manufacturers of infant formula milk follows had fulfil all the requirement in theories of marketing but somehow they did not follow the guideline as stipulated in the Code of Ethics in Malaysia. This research also reviews the definition and aspects of the international perspective on formula milk. In this research we discovered Malaysia is one of the country adopted International Code of Marketing of Breast milk Substitute and manufacturer of infant formula milk are not legally binding to the Codes. Besides, this research intend to analyse the Malaysian position in governing the issue of marketing of infant formula milk which highlight the functions of the bodies, committees and policies involved in the issue concerned. Then, several countries were being compared to, in analysing their implementation of the Code throughout this era where this research will highlight the monitoring of national policies and practices regarding the marketing of breastmilk substitutes in compliance with the International Code of Marketing of Breastmilk Substitutes in several international countries. Based on the majority opinion and also the research from WHO, they indicates that International Code of Breast milk should be implemented as regulation in worldwide. This research is conducted in order for Malaysia to implement the existing Code oof Ethics into regulation. As we concerned, throughout this research we found out there are some violation by the manufacturer of infant formula milk in Malaysia because there is lack of sanction and punishment if they violate the Code of Ethics. Based on the previous researched, it is confirmed that unrestrcited advertising of infant formula milk affects mothers decision to breast feed their child. This reseach paper also lays down several recommendation upon the conclusion that has been achieved. This research suggest all advertising and marketing of infant formula milk should be prohibited and all hospitals and clinics must comply with the Baby Friendly Hospital Initiative. Complainant process for the those who make complaints on the violation on marketing infant formula milk should be effectively revised and harsh punishment should be imposed in terms of imprisonment and fine for those who violated the Code. This study may impact the Faculty of Law of UiTM on the analysis on the legal aspect on marketing of infant formula milk.